Drug Development Against the Major Diarrhea-Causing Parasites of the Small Intestine, Cryptosporidium and Giardia - Miyamoto, Yukiko; Eckmann, Lars (Frontiers in Microbiology, 2015)
Diarrheal diseases are among the leading causes of morbidity and mortality in the world, particularly among young children. A limited number of infectious agents account for most of these illnesses, raising the hope that advances in the treatment and prevention of these infections can have global health impact. The two most important parasitic causes of diarrheal disease are Cryptosporidium and Giardia. Both parasites infect predominantly the small intestine and colonize the lumen and epithelial surface, but do not invade deeper mucosal layers. This review discusses the therapeutic challenges, current treatment options, and drug development efforts against cryptosporidiosis and giardiasis. The goals of drug development against Cryptosporidium and Giardia are different. For Cryptosporidium, only one moderately effective drug (nitazoxanide) is available, so novel classes of more effective drugs are a high priority. Furthermore, new genetic technology to identify potential drug targets and better assays for functional evaluation of these targets throughout the parasite life cycle are needed for advancing anticryptosporidial drug design. By comparison, for Giardia, several classes of drugs with good efficacy exist, but dosing regimens are suboptimal and emerging resistance begins to threaten clinical utility. Consequently, improvements in potency and dosing, and the ability to overcome existing and prevent new forms of drug resistance are priorities in antigiardial drug development. Current work on new drugs against both infections has revealed promising strategies and new drug leads. However, the primary challenge for further drug development is the underlying economics, as both parasitic infections are considered Neglected Diseases with low funding priority and limited commercial interest. If a new urgency in medical progress against these infections can be raised at national funding agencies or philanthropic organizations, meaningful and timely progress is possible i